Chamanismo y evangelismo entre los shipibo-konibo de San Francisco - Slaghenauffi, Doriane Sabine (Pontificia Universidad Católica del Perú, 2024)
In regular contact with urban civilization and the market economy, Shipibo-Konibo society today experiences a phenomenon of religious pluralization between, on the one hand, a marketing, in some villages, of vernacular shamanism aimed at a public of Western tourists in search of mystical and hallucinogenic experiences and, on the other, a growing implantation of protestant churches of different denominations. If, at first sight, this evolution can be analyzed as a form of acculturation, in the light of ethnography, the resulting religious cohabitation reactivates on the contrary a certain predation complex specific to the past, through both ontological and statutory rivalries that would be linked to a close proximity of the approaches of the two institutions.

En contacto regular con la civilización urbana y la economía de mercado, la sociedad shipibo-konibo conoce hoy un fenómeno de pluralización religiosa entre, por un lado, una comercialización, en algunos pueblos, del chamanismo vernáculo destinada a un público de turistas occidentales en busca de experiencias místicas y alucinógenas y, por otro, una implantación creciente de iglesias protestantes de diferentes denominaciones. Si, a primera vista, esta evolución puede analizarse como una forma de aculturación, a la luz de la etnografía, por el contrario, la cohabitación religiosa resultante reactiva un cierto complejo de predación propio del pasado, a través de rivalidades a la vez ontológicas y estatutarias que estarían vinculadas a una proximidad demasiado grande de los enfoques de las dos instituciones.
Shamanism and Evangelism Among the Shipibo-konibo of San Francisco
Keywords: Shamanism; Peruvian Amazon; Predation; Witchcraft; Evangelism; Shipibo-konibo; Chamanismo; Amazonía peruana; Depredación; Brujería; Evangelismo; Shipibo-konibo; https://purl.org/pe-repo/ocde/ford#5.04.03